Non-use of dentures after tooth loss is associated with elevated sodium/potassium ratios in older adults: a retrospective cohort study - Abe, Takafumi; Hamano, Tsuyoshi; Usuda, Haruki; Wada, Koichiro; Okuyama, Kenta; Tominaga, Kazumichi; Yano, Shozo; Isomura, Minoru (Frontiers in Dental Medicine, 2025)
ObjectiveAn elevated sodium-to-potassium (Na/K) ratio in urine increases the risk of hypertension. Tooth loss in older adults can lead to a diminished nutritional state, including alterations in the Na/K ratio. However, the relationship between denture use and changes in the Na/K ratio among individuals with tooth loss has not been sufficiently explored. This study examined whether denture use modifies the association between tooth loss and changes in the Na/K ratio.MethodsSurveys in 2016 and 2018 included 473 older adults. The Na/K ratio was measured using spot urine tests. A dental hygienist evaluated the number of teeth and the use of dentures. We used generalized linear models to analyze the combined effect of the number of teeth and denture use on changes in the Na/K ratio.ResultsParticipants without dentures in the 0–19 teeth group showed a significant association with changes in the Na/K ratio (B = 0.635; 95% confidence interval = 0.038, 1.232) compared to those with ≥28 teeth, but denture users with 0–19 teeth did not show significant association. No significant association with changes in the Na/K ratio was observed in denture users and non-users with 20–27 teeth.ConclusionIn non-denture users with fewer than 20 teeth, the Na/K ratio was markedly elevated, but in denture users with fewer than 20 teeth it was not significant. These findings highlight the importance of promoting denture use in older adults with few remaining teeth to maintain their Na/K balance.